Pengaruh Komitmen Organisasi dan Budaya Organisasi Terhadap Disiplin Organisasi di Polres Kerinci - Syamsir, Syamsir; Kuswandi, Rudi (Journal of Education on Social Science (JESS), 2025)
Studies regarding work discipline in police agencies or institutions are still relatively rare research in the realm of public administration research in Indonesia. This study was intended to analyze the effect of organizational commitment and organizational culture on organizational discipline among the police officers in the Kerinci Police Station. In the long term, this research aims to improve the quality of discipline of police officers in the delivery of services to the community, especially at the Kerinci Police agency, which so far seems to have not been optimal. One of the causes of the low quality of discipline is, among other things, assumed to be the impact of the low quality of commitment and organizational culture among the members of the Polres concerned. This study was conducted using a quantitative approach. The data were collected through distributing questionnaires as well as documentation data support. The data were analyzed with descriptive statistics consisted of frequencies, averages, percentages and multiple regression. The finding of this study indicated that organizational commitment and organizational culture did not significant influences on organizational discipline among the police officers in the Kerinci Police Station.